The role of elevated lipoprotein(a) in aortic valve disease: a systematic review - Wambua, P.; Wahinya, M.; Khan, Z. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCalcific aortic valve stenosis (CAVS) is the most prevalent valvular heart disease and a growing global health concern. Aortic sclerosis (ASc) and aortic stenosis (AS) represent a continuum of progressive disease characterized by leaflet thickening, inflammation, lipid deposition, and calcification. Lipoprotein(a) [Lp(a)], with its pro-atherogenic, pro-inflammatory, and pro-calcific properties, has emerged as a key contributor to this process. While its role in atherosclerotic cardiovascular disease is well established, the relationship between Lp(a) and CAVS has been demonstrated in several key studies; however, the available evidence remains limited in volume, and important gaps persist in understanding mechanisms, risk stratification, and therapeutic implications.MethodsA systematic literature search was conducted in PubMed, Cochrane Library, ScienceDirect, Medline, ResearchGate, Embase, and Google Scholar in accordance with PRISMA guidelines. Eligible studies included observational designs (cross-sectional, cohort, case-control) and randomized trials evaluating associations between Lp(a) levels, genetic variants, and CAVS. Study quality was assessed using the Newcastle–Ottawa Scale (NOS).ResultsEighteen studies met the inclusion criteria, comprising six case-control, six cohort, and six cross-sectional studies with a total of 153,192 participants. No randomized controlled trials were identified. Elevated Lp(a) levels were consistently associated with an increased risk of AS and aortic valve calcification (AVC), with a dose-dependent effect. The risk was highest at levels ≥50 mg/dl, though some evidence supported risk at ≥30 mg/dl. Genetic analyses identified rs10455872 as a significant risk allele, while rs3798220 showed inconsistent associations. Multi-ethnic cohorts highlighted racial variability: Afro-Caribbean individuals had higher baseline Lp(a) levels but lower AVC prevalence than Caucasians.ConclusionLp(a) is an independent risk factor for CAVS, influenced by both concentration and genetic variation. Early screening and emerging Lp(a)-lowering therapies, including antisense oligonucleotides, small interfering RNA, and PCSK9 inhibitors, may help mitigate disease progression. Further randomized trials are needed to determine whether Lp(a) reduction translates into cardiovascular and valvular benefit.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024533835, PROSPERO CRD42024533835.